Development of Integrated Student Worksheets (LKPD) of Al-Quran Verses on the Subtheme of How the Body Processes Clean Air for Grade V MI Students: Development Study with 4D Model - Bintang, Bintang; Muhaemin, Muhaemin; Mirnawati, Mirnawati; Fauzia, Rizkinur; Atmasudirja, Ivan Priyana; Da Costa, Mohammad Anwar (State Islamic Institute of Palopo, 2024)
This study aims to develop Student Worksheets (LKPD) on the subtheme